1, 3-Dipolar cycloaddition of uracil derivatives with nitrile oxides: Synthesis of [1, 2, 4]oxadiazolo[4, 5-c]pyrimidine-5, 7(6H)-dione derivatives. Issue 47 (23rd November 2017) - Jiang, Kun-Ming; Jin, Yi; Lin, Jun
Abstract: An efficient method of synthesizing bicyclic fused [1, 2, 4]oxadiazolo[4, 5- c ]pyrimidine-5, 7(6 H )-dione derivatives was developed through a [3 + 2] cycloaddition of uracil derivatives and nitrile oxides. In the one step reaction, CN and CO bonds were constructed, the target compounds were efficiently obtained in good yields. The method represents a valuable way to obtain highly functional fused bicyclic heterocycle derivatives in a simple, rapid and practical manner. The method fusing bicyclic heterocycles can be applied for modification of uracil analogues that may have potential biological activities. Graphical abstract: